Rough sets based on Galois connections - Madrid, Nicolás; Medina, Jesús; Ramírez-Poussa, Eloísa (Zielona Góra: Uniwersytet Zielonogórski)
Rough set theory is an important tool to extract knowledge from relational databases. The original definitions of approximation operators are based on an indiscernibility relation, which is an equivalence one. Lately, different papers have motivated the possibility of considering arbitrary relations. Nevertheless, when those are taken into account, the original definitions given by Pawlak may lose fundamental properties.
Keywords: rough sets; Galois connections; approximation operators